2008
DOI: 10.1038/cgt.2008.18
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of fiber-modified adenovirus-transfected dendritic cells to express HER-2/neu stimulates efficient HER-2/neu-specific humoral and CTL responses and reduces breast carcinogenesis in transgenic mice

Abstract: HER-2/neu transgene-modified dendritic cell (DC)-based vaccines are potent at eliciting HER-2/neu-specific antitumor immunity. In this study, we constructed a recombinant adenovirus RGD AdVneu with fiber gene modified by RGD insertion into the viral knob's H1 loop. We transfected DCs with RGD AdVneu, and assessed/compared HER-2/neu-specific humoral and cytotoxic T lymphocyte (CTL) responses and antitumor immunity derived from the original AdVneu-transfected DCs (DCneu1) and RGD AdVneu-transfected DCs (DCneu2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Now, DCs can be pulsed with synthetic peptides or proteins derived from known tumor-associated antigens (TAA) such as MUC1 [17], Her-2/neu [18], tyrosinase [19], CEA [20], or Melan-A/MART [21]. However, vaccinating against a single antigen has disadvantages, as it is unknown which of the identified antigens have the potential to induce an effective antitumor immune response [22].…”
Section: Discussionmentioning
confidence: 99%
“…Now, DCs can be pulsed with synthetic peptides or proteins derived from known tumor-associated antigens (TAA) such as MUC1 [17], Her-2/neu [18], tyrosinase [19], CEA [20], or Melan-A/MART [21]. However, vaccinating against a single antigen has disadvantages, as it is unknown which of the identified antigens have the potential to induce an effective antitumor immune response [22].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the CTL and humoral responses induced by DCneu2 vaccination were more important than those induced by DCneu1 vaccination. Immunization of FVB mice with the DCneu2-based vaccine protected 100% of the animals that were transplanted with a syngeneic tumor cell line, which over-expresses HER2 [41]. In addition, the same authors previously reported in a sideby-side study that a vaccine based on DCs transfected with an adenovirus encoding HER2 was more efficient than the DNA-based HER2 vaccine [42].…”
Section: Experimental Workmentioning
confidence: 85%
“…The addition of the RGD motif in the construct was reported to efficiently increase expression of HER2/neu. The authors transfected DCs with (RGD) AdVneu [(DCneu2 cells) or AdVneu alone (DCneu1 cells)] and then evaluated the anti-HER2 cellular and humoral responses as well as the anti-tumor effect [41]. In DCneu2 cells, HER2/neu expression was more than eight times higher than in DCneu1 cells.…”
Section: Experimental Workmentioning
confidence: 99%
“…40 The mouse breast cancer cell line Tg1-1 (H-2K q ) expressing rat HER2/neu was derived from a spontaneous breast cancer in FVBneuN mice. 37,38 Female wild-type C57BL/6 (H-2K b ) mice and transgenic CD11c-diphtheria toxin receptor (DTR) (H-2K b ) and FVB/N-Tg(MMTVneu)202Mul/J (FVBneuN) (H-2K q ) mice were obtained from Jackson Laboratories (Bar Harbor, ME, USA). All animal experiments were carried out in accordance to the Canadian Council for Animal Care guidelines.…”
Section: Reagents Cell Lines and Animalsmentioning
confidence: 99%
“…[32][33][34][35][36] We have previously shown that HER2/neu-specific DC vaccine stimulated more efficient HER2/neu-specific CTL responses and antitumor immunity than DNA vaccine. 37,38 Recently, we have demonstrated that DC vaccine-stimulated CTL responses were derived not only from the stimulation of CD4 þ T-cell-licensed DCs, but also from the stimulation of DC-primed CD4 þ T cells with acquired DC's peptide/MHC-I complexes by trogocytosis. 39 Therefore, we assume that DC vaccine containing the potent CD4 þ Th epitope P30 may stimulate enhanced CD4 þ T-cell responses, leading to more efficient HER2/neu-specific CTL responses and immunity against HER2/neu-positive breast cancer.…”
Section: Introductionmentioning
confidence: 99%